Safety Analysis of Gedebage Station Equipment Building against Vibration with Microtremor and PPV Methods - Febrinzaghi, Mohammad Gerald; Syafier, Siegfried; Sudarsono, Ignatius (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2025)
This study evaluates the impact of railway-induced vibrations on an equipment building near Gedebage Station, Bandung. Proximity to the railway track raised concerns about occupant comfort and structural integrity. The assessment employed microtremor analysis to determine natural frequencies of the soil (using HVSR method) and the building (using FSR method), alongside PPV analysis to measure vibration levels against regulatory standards. Results revealed that the train-induced vibration frequency ( 37 Hz) did not coincide with the buildings natural frequency ( 23 Hz), eliminating resonance risks. However, moderate natural resonance vulnerability was detected on the first floor in the east-west direction. While some PPV values exceeded Indonesias environmental thresholds (Kepmen LH) for minor plaster cracks (category B), all remained within DIN 4150-3 safety limits for commercial structures. In conclusion, the building faces no immediate structural threat, but train vibrations may cause minor non-structural disturbances, such as cosmetic cracks. Mitigation measures could enhance occupant comfort, though structural reinforcement appears unnecessary. The findings highlight the importance of vibration monitoring in infrastructure planning near railways.